“Aware-Settler” Biblical Studies: Breaking Claims of Textual Ownership - Matthew R. Anderson (University of Sheffield, 2019)
“Aware-Settler” is a term coined here to describe the various hermeneutics that arise as increasingly, non-Indigenous biblical scholars take seriously that their research is done on colonized Land. Paying special attention to the principle of possessiveness, the article suggests breaking stubborn Settler-scholar hidden-default assumptions of ownership, proposing instead that biblical texts might be understood as another form of “Treaty territory.” Indigenous scholars’ common emphases on Landedness, relationality, spirituality, and community good, can inform methodologies employed by Settler biblical scholars. These hermeneutical principles, learned in a contact zone characterized by attention to reciprocity and respect, are employed in a brief look at Matthew 28:25–28. The so-called Great Commission is a foundational text of colonialism; many Indigenous scholars have judged it as “unreadable.” For that reason it provides a particularly appropriate test-case for applying Aware-Settler hermeneutics focussed on breaking claims of identity and ownership.